Análise do perfil lipidômico e do risco cardiovascular na pré e pós menopausa - NOGUEIRA, Iara Antonia Lustosa (2017)
Menopause is a physiological process that affects women during their late 40s or early 50s, but it has substantial health consequences, varying from disturbances in the lipid and glucose metabolism to changes in sleep, increasing exposure to cardiovascular disease. The aim of this study was to analyze the lipid profile and cardiovascular risk in pre and post menopause, in order to better understand the possible mechanisms that increase cardiovascular risks after menopause. It was a cross-sectional analytical study, including evaluated 184 women aged to 40 to 65 years. Socio-demographic, clinical, anthropometric and laboratory data were obtained as well as comorbidities, such as diabetes, dyslipidemia, hypertension and metabolic syndrome. The stratification of cardiovascular risk in 10 years was performed using the Framingham equation and the overall risk score. A total of 40 participants blood samples of this total were randomly selected for serum lipidic analysis, using mass spectrometry. Participants mean aged of 50 (SD 6.8) years and 54.8% were defined as postmenopausal. From the Framingham score, most women were classified as low risk, with 95.1% frequency for cardiovascular disease in 10 years in premenopausal women and 74.5% in those postmenopausal, despite the high percentage of risk factors, such dyslipidemia (72.6%), metabolic syndrome (50%), insulin resistance (50.9%) and diabetes (16.7%) in postmenopausal. Stratification by the global risk score was more adequate, that is, 64.6% of premenopausal women and 29.4% of postmenopausal women were classified as low risk, whereas 22% and 62.8% were in the high risk category, respectively. In lipidic analysis, lipid species were found to have increased concentrations in postmenopausal women, with the most notable being ceramides (N.C23: 0.Cer; N.C23:0(OH).Cer and N.C24:0(OH).Cer) with Fold Change of 1.68, 1.59 and 1.58, respectively. It was also observed that 14 metabolites showed a significant difference between pre and post menopause, mainly ceramide species. Strong and positive correlations were identified between several metabolites with fasting glucose, glycated hemoglobin, total cholesterol, LDL and triglycerides. Highlight the associations between the species ceramides (N.C10:0.Cer) and lysophosphatidylethanolamine (LPE.a.C18:0) with fasting glucose (r = 0.83 and r = 0.73, p< 0.05 , respectively) and with glycated hemoglobin (r = 0.81 and r = 0.75, p <0.05, respectively). The data obtained allowed us to conclude that postmenopausal women h, ad a CVD risk that was approximately three times higher than in premenopausal women, and that the Framingham score seemed to underestimate cardiovascular risk in the climacteric, whereas the overall score stratified more adequately once which was consistent with the CVD risk factors observed in this population. However, the main findings of this study were the important lipid changes detected in postmenopausal women, especially in the class ceramides, as well as correlations with classical glycolic and lipid markers that may be useful to investigate diseases associated with this phase.